The Indonesian Government’s Response and Foreign Policy Values to The Formation of AUKUS - Ramelan, Michael Sanrio; Paji Suwarno; Irwan Triadi; Pujo Widodo; Achmed Sukendro (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This research discusses the Indonesian government's response and foreign policy implications for the formation of AUKUS (Australia, United Kingdom, United States) using a qualitative descriptive approach and constructivism theory. This research using qualitative descriptive method. Through a literature review, this research identifies that the formation of AUKUS has raised concerns among the Indonesian government regarding the potential for conflict escalation and its impact on regional stability, especially in the context of geopolitical competition between AUKUS and China in the Indo-Pacific region. This analysis highlights how constructivist views influence Indonesia's perception of developing regional security dynamics, where large countries compete with each other in global power arrangements. The results of this research provide insight into how Indonesia formulates diplomatic strategies to face new challenges in the regional security sphere, including efforts to maintain the balance of power and strengthen multilateral cooperation in responding to increasingly complex foreign policy dynamics. In conclusion, this research not only describes the Indonesian government's response to AUKUS contextually, but also outlines the foreign policy values ​​that underlie Indonesia's attitudes and policies in facing changing global security dynamics.